A159 VERY EARLY-ONSET INFLAMMATORY BOWEL DISEASE (VEO-IBD): CASE REPORT AND REVIEW OF THE LITERATURE. (1st March 2018) - Alahmari, A A; Nguyen, V; Morinville, V D; Ahmed, N; Sant'Anna, A
Abstract: Background: Inflammatory bowel disease (IBD) is a chronic inflammatory condition of the gastrointestinal tract, and its pathogenesis involves genetic and environmental factors. Very early-onset IBD (VEO-IBD) is a designation given to disease diagnosed before 6 years of age. This subgroup is often characterized by higher severity, aggressive progression, strong family history of IBD, predilection for colon-only involvement, and poorer response to conventional treatments. Immunodeficiencies are identified in up to 25% of cases, which may impact response, safety, and indication to different therapies. Aims: To describe a case of VEO-IBD and review of the literature. Methods: Case report and literature review. Results: We report a 6 month-old female that presented at 2 months with a history of fever, lethargy and bloody diarrhea after receiving standard 2 month-vaccinations (including rotavirus). Laboratory results demonstrated neutropenia (ANC 0.13), elevated inflammatory markers (CRP: 103–330 mg/L) and low albumin (16g/L), with a negative infectious work-up, including blood culture, stool culture, Clostridium difficile toxin, and viral serology (CMV). There was no improvement of bloody diarrhea on initial intravenous (IV) broad spectrum antibiotic coverage nor on exclusive elemental diet. Abdominal ultrasound showed mild circumferential wall thickening of transverse and descending colon with hyperemia compatible with colitis. An upper endoscopy and rectosigmoidoscopy revealed mild to moderate patchy chronic gastritis with several giant cells, a normal duodenum, and moderate to severe chronic patchy active colitis, suggestive of IBD. Due to early age of onset, a partial immunologic investigation was undertaken: chronic granulomatous disease, IL-10 and IL-10R pathway activity, were normal. A genetic panel to try to identify whether one of the genes identified in cases of VEO-IBD is planned. Sulfasalazine was attempted but, led to worsened abdominal pain, distention, and bleeding; IV methylprednisolone was started (1.0 and then 1.5mg/kg/day), with partial response (decrease blood in stools, but inability to progress enteral feeds). Upper and lower endoscopies were repeated after one month of steroid, showing decreased colonic inflammation and normalized gastric biopsies. However, due to only partial response, enteral vancomycin and tobramycin were added, as well as hydrocortisone enemas, which led to improved symptoms and feeding tolerance. Conclusions: VEO-IBD must be considered in infants with non-infectious bloody diarrhea unresponsive to hypoallergenic formula. More than 50 monogenic defects in innate and adaptive immune system have been associated with VEO-IBD and this is likely to grow with advances in genome sequencing. These disorders should be sought in VEO-IBD as positive findings may help guide more appropriate treatment. Funding Agencies: None